1992
DOI: 10.1111/j.1365-246x.1992.tb00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure of the west Bengal basin, India from deep seismic sounding investigations

Abstract: SUMMARY Basement and sub‐basement crustal configuration of parts of the west Bengal basin has been delineated from inverse and forward modelling of refraction and wide‐angle reflection data obtained along two east‐west profiles: (a) Beliator‐Burdwan‐Bangaon (profile‐1) about 180 km long and (b) Gopali‐Tamluk‐Port Canning (profile‐2) about 140 km long. The study has revealed the existence of four groups of prominent refractors (velocities 1.7–2.1 km s−1, 2.7–3.2 km s−1, 3.7–4.2 km s−1, and 4.6–5.3 km s−1) overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 5 publications
4
42
0
Order By: Relevance
“…2.12) is commonly identified as the Eocene palaeoshelf edge, marking the boundary of the thick sediment pile and associated with a sharp increase in depth of the shallow-water Sylhet Limestone (Alam 1989;Alam et al 2003). Deep seismic sounding lines crossing the hinge line confirm that the crust thins sharply here but it is concluded that, close to the hinge line, the evidence is consistent with thinned continental crust rather than with true oceanic material (Kaila et al 1992). Receiver functions sampling the crust immediately to the south of the Shillong Plateau also support this conclusion (Mitra et al 2005).…”
Section: Continent-ocean Transitionmentioning
confidence: 55%
“…2.12) is commonly identified as the Eocene palaeoshelf edge, marking the boundary of the thick sediment pile and associated with a sharp increase in depth of the shallow-water Sylhet Limestone (Alam 1989;Alam et al 2003). Deep seismic sounding lines crossing the hinge line confirm that the crust thins sharply here but it is concluded that, close to the hinge line, the evidence is consistent with thinned continental crust rather than with true oceanic material (Kaila et al 1992). Receiver functions sampling the crust immediately to the south of the Shillong Plateau also support this conclusion (Mitra et al 2005).…”
Section: Continent-ocean Transitionmentioning
confidence: 55%
“…The Bengal basin is covered by recent alluvium and bounded by the Indian Peninsula in the west, Lushai-Naga folded belt in the east, the Bay of Bengal in the south and Shilong Plateau in the north (KAILA et al, 1992). The basin has various step faults and thick Tertiary and Mesozoic sediments overlying the basement.…”
Section: Bengal Basinmentioning
confidence: 99%
“…The gravity data are digitized from the gravity map of the Bengal basin (which was compiled by the NGRI from gravity the data set from the Oil and Natural Gas Corporation, India and MUKHOPADHYAY et al, 1986 at an approximately average gravity station spacing of 1 km) along the seismic profiles, and further data are interpolated at 1-km interval. The deep seismic studies using refraction and wide-angle reflection methods are also carried out along these two profiles (KAILA et al, 1992;MALL et al, 1999;PRASAD et al, 2002). Seismic study maps the sedimentary column thickness, the basement and deep crustal structure.…”
Section: Bengal Basinmentioning
confidence: 99%
“…1(a)), also suggest plume-induced crust-mantle interaction (Tewari, 1998). A high velocity deep crust is inferred beneath the Bengal basin too (Kaila et al, 1992), which also exhibits a gravity high anomaly (∼20 mgal) sub-parallel to 90…”
Section: Geophysical and Tectonic Evidence Of Channelingmentioning
confidence: 99%